Empowerment of Riverside Communities in Sustainable Environmental Management (Study in Petuk Katimpun Village, Jekan Raya District, Palangka Raya City) - Saputra Adiwijaya; Purnama Julia Utami; Herlina Eka Shinta; Yovita (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
This study aims to analyze the empowerment of people who live and settle on the banks of the river in Petuk Katimpun Village, Jekan Raya District, Palangka Raya City, especially in stunting prevention efforts. Data were collected through in-depth interviews with 10 key informants who were considered to have distinctive characters. The data collected were analyzed by qualitative methods. The results of this study illustrate that there is a model in empowering riverbank communities because the character of the people who live on the banks of the river has its own characteristics and plus generally are Dayak ethnicities, people who live on the banks of the river are very dependent on all the potential of the river and its surroundings, especially in the field of fisheries with the karamba method. and the fish produced are partly a source of nutrition, then also by utilizing purun plants as their alternative livelihood. Then the position of the house on stilts occupied also affects the fisheries sector they manage. On the other hand, the flood impact caused losses to the fish seeds that were developed because they came from fertilizer residue from oil palm plantations upstream.